Colombia : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Colombia. (IMF Staff Country Reports; Country Report, 2021)
COVID-19 has taken a severe social and economic toll, including almost 60,000 deaths. With over 5 million jobs temporarily affected, Colombia recorded its largest recession on record. Since 2020H2, an uneven recovery with intermittent growth has been underway, led by private domestic demand. Staff expects only a gradual recovery in 2021 with economic activity not expected to return to pre-pandemic levels until the second half of 2022. Vaccinations began in February with plans to effectively cover the adult population. However, both external and domestic risks remain skewed to the downside.